2022
DOI: 10.3389/fpsyt.2022.933514
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Mental Health Status of Dentists Under COVID-19 Epidemic

Abstract: ObjectiveTo investigate dentists’ psychological status and influencing factors in Shaanxi Province during the COVID-19 epidemic and assess their perceived wellness.MethodsThe study was conducted among dentists from Shaanxi Province in China. The basic information was collected through the network questionnaire star platform. Depression, Anxiety, and Stress Scales (DASS-42) and Perceived Wellness Survey (PWS) were used to assess subjects’ psychological status and perceived wellness. Univariate linear regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A survey of 3236 general practitioners in China showed that 313 (9.67%) had low occupational stress, 1028 (31.77%) had medium occupational stress, and 1895 (58.56%) had high occupational stress [ 13 ]. A survey of 256 dentists in Shaanxi Province of China showed that 34.4% of dentists had occupational stress [ 14 ]. In Vietnam, the results of a cross-sectional study on occupational stress in dermatology medical staff showed that 6.4% of medical staff had occupational stress [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A survey of 3236 general practitioners in China showed that 313 (9.67%) had low occupational stress, 1028 (31.77%) had medium occupational stress, and 1895 (58.56%) had high occupational stress [ 13 ]. A survey of 256 dentists in Shaanxi Province of China showed that 34.4% of dentists had occupational stress [ 14 ]. In Vietnam, the results of a cross-sectional study on occupational stress in dermatology medical staff showed that 6.4% of medical staff had occupational stress [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large portion of these studies have examined symptoms and coping strategies for mental health issues such as anxiety and depression etc 6 8 . Others have analyzed the factors affecting people’s mental health during the COVID-19 pandemic 9 11 . The factors proposed in these empirical studies were diverse and cover different research objects such as students, patients, and medical caregivers, etc 12 14 .…”
Section: Introductionmentioning
confidence: 99%